2016
DOI: 10.1038/ajg.2016.257
|View full text |Cite
|
Sign up to set email alerts
|

Lower Observed Hepatocellular Carcinoma Incidence in Chronic Hepatitis B Patients Treated With Entecavir: Results of the ENUMERATE Study

Abstract: OBJECTIVES:Data from the United States are lacking regarding the impact of entecavir (ETV) on the risk of hepatocellular carcinoma (HCC). Our aim is to determine whether treatment with ETV is associated with a reduced HCC risk by calculating the expected HCC incidence based on the Risk Estimation for Hepatocellular Carcinoma in Chronic Hepatitis B (REACH-B) model and comparing it with the observed HCC incidence. METHODS:The incidence of HCC in US patients treated with ETV between 2005 and 2013 in a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…In their study, only 30% of the population were Asians, and predicted cases with respective SIR were only determined at the time of each incident HCC instead of using a yearly estimate. Another American study with 841 entecavir‐treated patients followed up to 8.2 years also showed similar findings . The majority (84%) of the subjects were Asians.…”
Section: Discussionsupporting
confidence: 55%
“…In their study, only 30% of the population were Asians, and predicted cases with respective SIR were only determined at the time of each incident HCC instead of using a yearly estimate. Another American study with 841 entecavir‐treated patients followed up to 8.2 years also showed similar findings . The majority (84%) of the subjects were Asians.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have demonstrated that antiviral therapy might reduce the risk of HCC. (Table ) Their limitations include studying a small proportion of patients with cirrhosis (9%‐33% of all patients) and a relatively short duration of antiviral therapy. The indications and regimens for NUC therapy and the patient populations were heterogeneous and thus not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the 5‐year cumulative incidence of HCC was 26.4% in the untreated cohort and 11.3% in the entecavir cohort. Several European and American studies using the HCC risk scores (REACH‐B, CU‐HCC and GAG‐HCC) for comparison because of unavailable control groups . Unexpectedly, the benefit of NUC therapy were found only in non‐cirrhotic rather than cirrhotic subgroups, probably because of small number of cirrhotic patients and these HCC risk scores might not be a good reference in cirrhotic patients undergoing NUC therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the goal of antiviral treatment being to decrease the morbidity and mortality associated with chronic hepatitis B (CHB), the first‐line antiviral agents recommended for treating CHB patients by the American Association for the Study of Liver Diseases (AASLD) include pegylated interferon, entecavir, and tenofovir . With their easy tolerability and efficacy in suppressing viral replication associated with high genetic barrier to resistance, many patients with HBV worldwide were treated with either oral agent, often achieving reversal of cirrhosis and reduced incidence of HCC …”
mentioning
confidence: 99%